Pengaruh Pemahaman Siklus Akuntansi, Computer Attitude, Intensitas Latihan Soal dan E-Learning terhadap Hasil Belajar Komputer Akuntansi - Yuliana Yuliana; Agung Listiadi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The research objective was to prove the effect of understanding the accounting cycle, computer attitude, question practice intensity and e-learning simultaneously (together) or partially (alone) on the learning outcomes of accounting computer learning. This type of research is a quantitative research. The analysis technique used multiple linear regression test assisted by the SPSS 25 application program. The research sample consisted of 125 students from class XI AKL SMK Negeri 1 Pati, which was taken randomly based on the proportional random sampling method and using the calculation of the Slovin formula. Data collection techniques are using tests, questionnaires and documentation. The results of the study proved that the understanding of the accounting cycle, computer attitude, question training intensity and e-learning influenced the learning outcomes of class XI AKL SMK Negeri 1 Pati. Acquisition of t test results prove that each variable, namely the understanding of the accounting cycle, computer attitude, the intensity of question exercises and e-learning partially affect the learning outcomes of accounting computer. Based on the research results, it is hoped that further researchers can develop this research, by expanding the scope of the research sample and adding variables that are thought to affect the learning outcomes of accounting computers such as learning styles, learning discipline, English language skills and computer mastery.